(untitled) (Scientia Agropecuaria, 2019)
Arbuscular mycorrhizal fungi (AMF) are organisms that form mutualistic associations with most plants, favoring their development, especially those located in degraded areas. In order to identify the different predominant native AMF morphotypes, and determine the percentage of colonization, and spore density in soils of the Cumbaza sub-basin in San Martin, Peru, soil samples were taken from degraded areas of Chirikyacu, Vista Alegre, El Chontal, San Antonio de Cumbaza, Aucaloma and Shapumba, and they were associated with 4 legumes cover crops among them, Cajanus cajan, Canavalia ensiformis, Crotalaria juncea and Vigna unguiculata. A completely random design was used, considering 6 zones and 4 legumes with 3 replications. The results showed that the treatments with legumes had greater influence in the mycorrhizal colonization in comparison with the zones of study, being Vigna unguiculata the one that had greater colonization (75%). However, the number of spores was influenced mainly by the zones, where the Aucaloma treatment had the highest number (252 spores / 10 g of soil). Eleven native AMF morphotypes were identified, being those of the genus Acaulospora the most predominant.